Adsorption characteristics of As(III) by schwertmannite: new findings in mineral-phase transformation and microbial effects - Li, Hao; Song, Wenjie; Li, Zhichao; Wang, Wei; He, Jiang; Lü, Changwei (Frontiers in Environmental Science, 2024)
The amount of As(III) adsorbed and the interfacial process are closely associated with the phase transformation of Schwertmannite (SCH). At present, studies on the adsorption characteristics of As(III) on SCH and the accompanying phase transformation process, especially the related mechanisms under the mediation of iron-reducing bacteria (FeRB) and sulfate-reducing bacteria (SRB), are limited in existing literature. With the help of continuous characterization, the adsorption behavior of As(III) on SCH was explored, as well as the transformation processes of SCH during these processes. The findings revealed that the SCH, synthesized by the KMnO4 oxidation and ethanol modification methods, exhibited excellent physical adsorption capacity for As(III) due to their increasing specific surface area and porosity. At room temperature (20 °C), the saturation adsorption capacities of As(III) by M-SCH and Y-SCH reached 62.69 and 58.62 mg/g, respectively. Moreover, the generation and phase transformation of As(III)-bearing ferrihydrite were observed within a 60-minute timeframe. It is the first time this phenomenon has been observed in such a short time, which is presumed to be an intermediate stage in the transformation of SCH into goethite. Furthermore, both FeRB and SRB could enhance the adsorption capacity of SCH for As(III). Comparatively, SRB has a more substantial impact on SCH's phase transformation. These insights are valuable for the practical application of SCH in treating As(III) pollution.